Pre-test estimation in the linear regression model under stochastic restrictions - Wijekoon, P.; Trenkler, G. (University of Peradeniya. Peradeniya, 1995)
In this paper, a general method to find stochastic properties of various stochastic pre-test estimators and forecasts is developed. This method is applicable if the convariance matrix O of the prior information is nonsingular.
Keywords: Mathematics; Matrices; Linear regression